Controlling Invasive Exotic Plants in North Florida Forests - Chris Demers; Alan Long; Rick Williams (EDIS)
Revised! SS-FOR-19, an 8-page fact sheet by Chris Demers, Alan Long, and Rick Williams, describes many of the current methods being used to manage some of the more common and troublesome invasive exotic plants in north Florida forests. Includes tables of herbicide recommendations and references. Published by the UF School of Forest Resources and Conservation, June 2008.